The factors influencing work-life balance among gen Y during pandemic Covid-19 in Malaysia - Nurul Asyiqin, Abu Samah (2022)
Work-life balance (WLB) has recently taken the attention of both scholars and organizational members and the widespread interest is due to the pandemic Covid-19 circumstances. The pandemic has caused many organizations to adopt work from home arrangement whereby if not properly managed can lead to work life imbalance. Understanding the factors that may influence WLB is important so that proper policy can be developed to ensure effective implementation of work from home arrangement. Therefore, this study aims to examine the factors influencing work-life balance among Gen Y during pandemic Covid-19 in Klang Valley. Employees in Gen Y group were chosen as they contribute to highest number in today’s workforce. The dependent variable is work-life balance, while the independent variables are perceived organizational support, perceived supervisory support, and self-efficacy. Data have been collected in various industry (i.e. banking, oil and gas, fashion retail, manufacturing, education, medical, food retail and etc.) located in Klang Valley area. The survey employed five points likert scales. Using SPSS version 26, Pearson correlation analysis was applied to test the relationship between perceived organizational support, perceived supervisory support, and self-efficacy and work-life balance. Furthermore, multiple regression analysis was used to investigate the effect of perceived organizational support, perceived supervisory support and self-efficacy on work-life balance among Gen Y during pandemic Covid-19. Based on the Pearson correlation results, all the independent variables have a positive relationship with work-life balance. On the other hand, regression analysis found that only perceived organizational support and self-efficacy have significant effect on work-life balance among Gen Y during pandemic Covid-19. Hence, based on the findings of this study, it is suggested that in order to enhance work life balance among Gen Y, organizations need to pay attention to providing appropriate organizational support and developing employee’s self-efficacy.